Identifikasi Administrasi Peserta Didik Pada SMA N 1 Labuhan Deli, Sumatra Utara - Nasution, Anggi Dwi Rosidi; Rangkuti, Mhd Alfin; Padang, Taufik Febriansah (MultiTech Publisher, 2023)
This research aims to identify the student administration system, assess the efficiency of software usage, and identify challenges faced by SMA N 1 Labuhan Deli in managing student data, particularly in the context of new student admissions. The research method used is a qualitative approach with a case study as the framework. The results show that the student administration system in the school has progressed, especially in the use of software to manage data. However, there are challenges in the admission of new students involving complex administrative processes. The efficiency of using software to manage student data requires improvement, although it has positively contributed to facilitating administrative tasks. The main challenges involve better data integration, staff training needed to operate the software effectively, and improved coordination among units in the school. The findings of this research provide valuable insights for researchers, as well as for SMA N 1 Labuhan Deli in developing a more efficient and effective student administration, especially in the context of new student admissions and student data management